USM RECEIVES THE FIRST NMR700MHz MACHINE IN ASIA-PACIFIC, RAISES CAPACITY OF HIGH-IMPACT RESEARCH - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 17 April 2016 – Today marked yet another historic moment for Universiti Sains Malaysia (USM) when it received the NMR700 MHz machine, purchased together between the Ministry of Science, Technology and Innovation (MOSTI) and USM from Bruker Corporation.